Acrylate–vinylidene chloride copolymers derived from corresponding water‐borne latexes: Influence of acrylate units on their potential as heavy‐duty anticorrosive coating materials. Issue 8 (24th November 2013) - Fu, Ce; Qin, Hong‐Wei; Ben, Hai‐Jie; Han, Jing; Cui, Wen‐Zhu; Cheng, Fa; Chen, Yu
Abstract A series of aqueous latexes with solid contents of 56%–59% were synthesized by binary emulsion copolymerization of vinylidene chloride (VDC) with an acrylate, namely methyl acrylate (MA), ethyl acrylate (EA), butyl acrylate (BA), hexyl acrylate (HA), or 2‐ethylhexyl acrylate (EHA). Differential scanning calorimetry (DSC) and Fourier‐transform infrared (FTIR) spectroscopy showed that the acrylate units with short ester side‐chains, such as MA and EA, made the copolymers hard and the crystallization tendency of their PVDC segments was reduced. Hydrophobic acrylates with relatively long ester groups, such as HA and EHA, gave flexible copolymers, and favored the crystallization of their PVDC segments. BA endowed the copolymers with medium flexibility and crystallization tendency. As coating materials, the copolymers bearing MA and EA adhered poorly to the tinplate before or after 100 hr of salt‐spray corrosion, whereas those bearing BA, HA, or EHA showed good adhesion to tinplate when they had little or no crystallinity. After 100 hr of salt‐spray corrosion, only BA–VDC80, containing 80% VDC, retained both excellent adhesion to metal and excellent barrier performance. Further study demonstrated that BA–VDC80 could protect tinplate from rusting for at least 250 hr under harsh salt‐spray corrosion. Scanning electron microscopy, FTIR‐attenuated total reflectance spectroscopy and DSC were used to evaluate the corroded BA–VDC80 film. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40192.